HYBRID LEARNING DALAM PEMBELAJARAN KOSA KATA BAHASA ARAB PADA ANAK BERBANTUAN MEDIA AL-MUTHO - Nuril Mufidah; Umi Salamah; Imroatul Muthoharoh; M. Irfan Islamy (Al-Mudarris: Journal Of Education, 2019)
This study aims to develop learning media in the form of videos called "Al-Mutho" videos on Haalatul Hadiiqoh material in third-grade students of elementary school. This is qualitative descriptive research and type of case study that aims to determine students' perceptions in using â€˜Al-Muthoâ€ videos. The results showed that students felt happier and eager to learn vocabulary (mufrodat) by using the video "Al-Mutho." Also, students are also able to remember ten new vocabulary words that are taught in one time face to face. This can be seen from the ability of students to answer the questions given quickly and precisely. Based on the results of the study it can be concluded that the video "Al-Mutho" can be used as an alternative media for mufrodat learning in Arabic for elementary schools.Â